Processed Bathymetry Grids (NetCDF:GMT format) derived from ship-based Multibeam Sonar Data from Antarctica - Ross Sea acquired during the Nathaniel B. Palmer expedition NBP0702 (2007) (IEDA: Marine-Geo Digital Library, 2007)
This data set was acquired with a ship-based Kongsberg EM120 Multibeam Sonar system during Nathaniel B. Palmer expedition NBP0702 conducted in 2007 (Chief Scientist: Dr. Stan Jacobs; Investigator(s): Dr. Frank Nitsche). These data files are of NetCDF Grid format and include gridded Bathymetry data and were processed after data collection. Data were acquired as part of the project(s): The Amundsen Continental Shelf and the Antarctic Ice Sheet, and funding was provided by NSF grant(s): ANT04-40775.